Key Factors of Joint-Liability Loan Contracts: An Empirical Analysis - Alexander S. Kritikos; Denitsa Vigenina (European University Viadrina, Department of Business Administration and Economics, 2005)
We empirically examine the efficacy of various incentives of microlending contracts such as joint-liability or group access to future loans. We find that joint liability induces a group formation of low risk borrowers. Furthermore, the incentive system leads to peer measures between the borrowers, helping the lender to address the moral hazard and enforcement problem. We also demonstrate that the mechanism realizes high repayment rates, if the loan officers fulfill their complementary duties in the screening and enforcement process. Finally, we show that dynamic incentives have to be restricted if the two problems of joint-liability are to be tackled notably.
Keywords: O22; G21; D82; 330; Mikrofinanzierung; Klein- und Mittelunternehmen; Kreditsicherung; Unternehmenskooperation; Schätzung; Georgien; Group lending